EVALUATION OF EMERGE LAND FOR MANGROVE CONSERVATION PROGRAM IN KALIWLINGI, BREBES DISTRICT, BREBES REGENCY - Aditya Dwi Nugroho; Muhammad Helmi; Jusup Supriijanto (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2020)
Mangrove ecosystems are very important in the balance of ecosystems in coastal areas, because many mangrove functions cannot be replaced by other ecosystems or vegetation from physical, ecological to economic functions. The mangrove ecosystem is decreasing along with the development of coastal areas construction, reclamation, and natural factors including coastal abrasion. This study aims to evaluate emerge land for the mangrove rehabilitation conservation program in Kaliwlingi, Brebes Regency. The imagery used is Landsat satellite imagery and Sentinel in 1999, 2004, 2009, 2014, and 2019. Image processing is done with the support of ER Mapper 7,0, Arc GIS 10,2,2, The method of determining land for mangrove rehabilitation includes the physical conditions of the waters and the analysis of the sediment’s grain size.   Adjustment area of abrasion in Kaliwlingi, Brebes Regency from 1999 to 2019 were 121,42ha, 109,32ha, 102,98ha and 151,57ha, respectively, Meanwhile, there are 4 points of emerge land found in the research location, With the units of abrasion value in Kaliwlingi, Brebes Regency and  emerge land can be used as mangrove rehabilitation area.